Vivências dos profissionais da atenção primária à saúde com a caderneta de saúde da criança - Gisele Nepomuceno de Andrade (2011)
Organization of children health care n prmary attention is based on actions of health promotion and surveWance. Child health records are an essential instrument when dev&oping those actions, This study had the goal to understand the meaníng of the experience of primary attenton health professional when dealing with the childs health records. To reach thís goal, qualitative research was used, oriented by the phenomenological referentiaL The research took place in two heafth centers in the city of Belo Horizonte, Brazil. Ten professionais of the family health program participated in the research, including nurses, doctors and two pediatricians who integrate the support team. Data coliection was made via interview guided by the following questions: Teu me, how your experience with the childs health records is? How is it, to you, the filling of the records? Data was analyzed based on Martins and Bicudo (2005), who define how to apply discourse analysis in the phenomenological approach. lnterview analysis converged to three categories: 1- The experience with the childs health records: between the real and the ideal. Shows the discussions that the participants had regarding the records and its health practices; 2- Chailenges when using the records: difficulties experienced in the professional world. Explains the complexity revealed by the professionals when using the records during the childs health practices. 3- How the professional perceives the involvement of the mother and the family with the records. Focuses on the importance of the rnother and of the family in the actions regarding the records. When reflecting about the meaning of the professional experience with the records and health attention, it was possible to perceive that this is filled with diffículties. The difficulties are derived from the knowledge limitations regarding the instrument; from the non-complementation of the records by many professionais who assist the child; from the daíly problems of the work and organizations of teams from the fami)y hea)th program, whích make the use of the records more difficult; from the lack of interest and care of the families regarding the instrument. Research points to possible and necessary ways to improve the use of the records as an integral surveillance instrument of children care.